2017
DOI: 10.1051/ps/2017018
|View full text |Cite
|
Sign up to set email alerts
|

Small and large scale behavior of moments of Poisson cluster processes

Abstract: Poisson cluster processes are special point processes that find use in modeling Internet traffic, neural spike trains, computer failure times and other real-life phenomena. The focus of this work is on the various moments and cumulants of Poisson cluster processes, and specifically on their behavior at small and large scales. Under suitable assumptions motivated by the multiscale behavior of Internet traffic, it is shown that all these various quantities satisfy scale free (scaling) relations at both small and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, we have shown that, even on real data, closed-form approximations can be utilised without severe consequences. Optimising a likelihood is slower than methods that rely on simple arithmetic computation (such as the moments-based estimators of Hohn et al (2003) and Antunes et al (2017)). Computation also increases with higher degrees of packet thinning (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we have shown that, even on real data, closed-form approximations can be utilised without severe consequences. Optimising a likelihood is slower than methods that rely on simple arithmetic computation (such as the moments-based estimators of Hohn et al (2003) and Antunes et al (2017)). Computation also increases with higher degrees of packet thinning (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Renewal processes form a natural context for internet traffic and have previously been used extensively in traffic analysis (e.g. Pipiras, 2011, 2016;Antunes et al, 2017;González-Arévalo and Roy, 2010;Hohn et al, 2003;Hohn and Veitch, 2006;Williamson, 2001). However, Williamson (2001) argues that simple renewal processes are limited in their ability to jointly model packet-level burstiness and the interaction between flows.…”
Section: The Bartlett-lewis Traffic Modelmentioning
confidence: 99%
See 3 more Smart Citations